O feminino na escrita de Clarice Lispector: a via crucis do corpo - Donadeli, Luciana Macedo (2017)
The articulations between psychoanalysis and literature are no longer new for academic studies, but the Freudian maxim about poets as holders of truth about the human still stands as truth to be considered by scholars, whether these psychoanalysts or literary. However, in order to find in fiction and literature real fictions about the human, it is necessary for the analyst to lend his body to the reading of the text, establishing a transferential reading next to his object of research. Through this loan, in which the analyst-researcher occupies the place of interlocutor with the text, it became possible, in this research, a subjective apprehension of a field that establishes itself in the contact between writer-text-reader in which he is able To perceive the logic that permeates this field, being able to break it by the application of the interpretative method. The application of the psychoanalytic method (interpretation) in Clarice Lispector's work A via crucis do corpo (1999a) was intended to capture a logic existing in the field that was erected in the contact of the researcher and some of the female characters contained in the plots chosen within this work. Based on the perceptions of this logic, a proto-theory was developed capable of being applied in the writing of the author Clarice Lispector as a whole, in order to apprehend her not only as a writer exposed by her work but also as a woman. For this, the Freudian and Lacanian theory, articulated by different authors, about the feminine and the woman, were used as background for the apprehension of the logic of the transferential field and for the interpretation of all the women that will be presented throughout this work, Including this researcher. Thus, it was possible to observe the movement of Clarice Lispector's characters towards a rupture of their identities, which led them to the need to reconstruct a new image for themselves. From this perception about women fictionalized in the narratives, it was possible to apprehend a fictionalization of the writer Clarice Lispector about her place as a canonized woman-writer and considered as serious and haughty, in an attempt to break with a rigid previous identity construction, which corroborated with a stereotype that Were used at the time, and opened space for a potential creative identity, in which the author can invent and reinvent herself, without having to find or determine an answer about her feminine condition, thus making it plural and performing maintenance Of the feminine enigma.